Comparative efficacy of calcarea phosphorica versus calcium hydroxide materials for the disinfection of remaining carious dentin in deep cavities: An In vivo study - Saritha Sirikonda; D Sravanthi; Kotagiri Swetha; Swetha Reddy Ankireddy; Shamama Shereen; Mohnish Zulfikar Manra; Kola Srikanth Reddy (Wolters Kluwer Medknow Publications, 2020)
Objectives: The aim of the study was to comparatively evaluate the efficacy of clinical and radiographic effects of calcarea phosphorica (CP) and calcium (Ca)(OH)2(Dycal) in indirect pulp capping of permanent teeth over a period of 6 months. Methodology: Permanent teeth were selected from children between the age group of 7 and 12 years, of which 20 teeth were considered, each for indirect pulp capping with CP and Ca(OH)2, respectively. Increase in dentin thickness was measured at baseline, 3 month, and 6 month on digitized radiographs using CorelDraw software. Results: Independent t-test had indicated that at the end of 3 and 6 months, a statically significant increase in dentin thickness with both CP and Dycal (P ≤ 0.001) was found within the CP group; the thickness of dentin formed was 0.089 mm ± 0.031 mm at first 3 months and 0.055 ± 0.022 mm at the second 3 months (P ≤ 0.001) evaluated using paired t-test. In the Dycal group, increment in dentin deposited was 0.068 mm at the first 3 months and second 3 months. It was 0.030 mm (P ≤ 0.001). Conclusion: Both clinically and radio graphically, CP is superior to Dycal as indirect pulp capping medicament in permanent teeth.